Effects Elicited by Compost Tea on the Primary Metabolome and the Nutraceutical Quality of Radish Root - Adele Fasolino; Maria Luisa Graziano; Massimo Zaccardelli; Valentina Tranchida Lombardo; Pierluigi Mazzei (Horticulturae)
It is desirable to find and evaluate innovative sustainable products guaranteeing and increasing the quality and productivity of radish (Raphanus sativus). Compost tea (CT) represents a natural organic preparation providing benefits to the soil–plant system, including a biostimulant action against climate change. Therefore, we evaluated whether CT can influence radish nutraceutical properties and its primary metabolism. In particular, the roots resulting from CT treatment were examined via conventional (total antioxidant and phenol contents) and spectroscopic techniques (high-resolution NMR and NIR) and compared with controls. It was proved that CT exerted a positive effect on the radish quality, which led to a significantly larger size in those treated (TRT), accompanied by higher contents of total antioxidants and phenols. The assignment of 1H and 13C signals in the NMR spectra allowed the delineation of the NMR fingerprint of the radish primary metabolome, which was processed by multivariate statistical analyses (PCA, PLS-DA, and heatmap clusterisation). TRT metabolites exhibited a peculiar profile, characterized by higher levels of glutamine and malic acid, along with lower levels of glucose, fructose, sucrose, lactic acid, and tryptophan. NIR spectroscopy also identified a recognisable profile in TRT, confirming its role as an alternative and accessible technique to appreciate the organic treatment’s effects on radish.